1993
DOI: 10.1080/07448481.1993.9936315
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Risk Behaviors and the Potential for Violence: A Look at What's Coming to Campus

Abstract: This study analyzed the types and predictors of violent behaviors reported by students in Grades 11 and 12 in South Carolina. Results are based upon responses of 2,299 students from 57 schools, approximately 3% of the total state enrollment in those grades. The 70-item self-report Youth Risk Behavior Survey developed and piloted by the Federal Centers for Disease Control was used to collect data. The authors performed a series of logistic regression analyses to explore the relation of the demographic and poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 11 publications
1
17
0
1
Order By: Relevance
“…Empirical evidence on the correlates of weapon carrying suggests that this risk behavior is indicative of, and associated with, violent behavior and used for purposeful criminal activity for urban and inner-city adolescents rather than self-protection (DuRant et al, 1994;Valois et al, 1993). Studies analyzing data from the national and selected state youth risk behavior surveys found that weapon carrying is inter-correlated with other adolescent risk behaviors, including fighting that involves injuries, substance abuse, school truancy, and sexual risk-taking, thus suggestive of a syndrome of risk/antisocial behavior among troubled youth Sosin et al, 1995;Orpinas, Basen-Enquest, & Grunbaum, 1995;Valois et al, 1993Valois et al, , 1995Valois & McKeown, 1998). The study of handgun ownership among high school students in Seattle, Washington, by Callahan and Rivara (1992) lends support to the theory that weapons are associated with aggressive and violent behavior, delinquency, and other risk behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence on the correlates of weapon carrying suggests that this risk behavior is indicative of, and associated with, violent behavior and used for purposeful criminal activity for urban and inner-city adolescents rather than self-protection (DuRant et al, 1994;Valois et al, 1993). Studies analyzing data from the national and selected state youth risk behavior surveys found that weapon carrying is inter-correlated with other adolescent risk behaviors, including fighting that involves injuries, substance abuse, school truancy, and sexual risk-taking, thus suggestive of a syndrome of risk/antisocial behavior among troubled youth Sosin et al, 1995;Orpinas, Basen-Enquest, & Grunbaum, 1995;Valois et al, 1993Valois et al, , 1995Valois & McKeown, 1998). The study of handgun ownership among high school students in Seattle, Washington, by Callahan and Rivara (1992) lends support to the theory that weapons are associated with aggressive and violent behavior, delinquency, and other risk behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties in coping with stress and the challenges of adolescent psychosocial development could mediate the relationship between adolescent life dissatisfaction and the inability to cope with body weight or body image dissatisfaction. In a general sense, many adolescents are not "life skilled" in five domains: communication, stress management, decision making, problem solving, and goal setting (Valois et al, 1993). Adolescents dissatisfied with life might engage in inappropriate dieting behaviors as a result of poor communication, decision making and problem solving attempts related to unfulfilled aspirations and needs.…”
Section: Discussionmentioning
confidence: 99%
“…Para as drogas ilícitas, Valois et al 24 descrevem riscos maiores nos usuários. Hall et al 12 defendem que isto decorre principalmente das condições socioeconômicas.…”
Section: Discussionunclassified